SCOPE OF NEP 2020, NCF-FS 2022, AND NCF-SE 2023 IN ADDRESSING THE EDUCATIONAL NEEDS OF GENERATION ALPHA AND BETA - G. Thirumoorthy; Sharma , Dr. Shesh Kumar; Datt , Ganesh (International Journal of Research -GRANTHAALAYAH, 2026)
Generation Alpha and Beta are poised to flourish in the wake of the catastrophic shift in artificial intelligence (AI) and robotics, which is poised to detach from the present, custom-bound society. Hence, it is of the hour that Generation Alpha and Beta need to accelerate through Education 4.0 to 5.0 to navigate and accommodate them into the Fourth and Fifth Industrial Revolutions (Industry 4.0 & 5.0), and they will witness the emergence of the Super Smart Society 5.0. Keeping these as a background, this article aims to describe the scope of NEP 2020, NCF-FS 2022, and NCF-SE 2023 in facilitating the transformation from Education 4.0 to 5.0 and in addressing the needs of Generation Alpha and Beta in India.